Indicators of the cyclically adjusted budget balance: The Bank of Finland's experience - Anne Brunila; Juhana Hukkinen; Mika Tujula (Bank of Finland, 1999)
Cyclically adjusted government budget balances have become increasingly popular as a means of analysing the fiscal situation and changes in policy that result from the intentional actions of the government.As the actual budget balances are affected both by cyclical factors ('automatic stabilisers') and structural ('discretionary') measures, they may not, in general, be very useful when seeking to assess the orientation of underlying fiscal policy and possible structural imbalances in the budget balance. The problem however is that there is no generally accepted method of calculating cyclically adjusted (structural) budget balances. The results tend to be fairly noisy and sensitive to the method of calculation.The purpose of this article is to highlight these issues by reviewing three estimation methods used by the Bank of Finland - GDP smoothing based on the Hodrick-Prescott trend estimation method, the production function approach and Blanchard's method - and the corresponding estimates of the cyclically adjusted budget balances for Finland.
URN:NBN:fi:bof-20140807369
Keywords: 330; fiscal policy; cyclically adjusted budget balance